De la dédiasporisation des jeunes Haïtiens à New York - Stéphanie Melyon-Reinette (Études Caribéennes)
The Push factors of Haitian emigration have completely changed since the late 1950s which marked the beginning of this movement with the Duvalier regime. The geopolitical and sociopolitical entities which result from it are changing as well, in proportion and accordance with the motivations of the people who leave. Thus, the forced exiles dreamt of going back to their dearest Haiti, the latest newly-arrived immigrants are individuals who desire to re-root into a land that sounds like “elsewhere”. Must the diasporic individual’s identity be stable? In this article, a simple survey seeks to shed light on the changing mentalities of young Haitians, examining their identities and cultural choices. Emerging trends show that diaspora is a flow, not unlike the identities and the cultures of which it is composed.